2021
DOI: 10.1136/jim-2021-001788
|View full text |Cite
|
Sign up to set email alerts
|

Allergic diseases influence symptom severity and T lymphocyte subgroups of children with tic disorders

Abstract: Tic disorders (TD) are childhood-onset neurological disorders. Immune system dysregulation has been postulated to play a role in TD, and its mechanisms likely involve dysfunctional neural-immune cross-talk, which ultimately leads to altered maturation of the brain pathways that control different TD clinical manifestations and behavioral and emotional damages. Clinical studies have demonstrated an association between TD and allergies and overactive immune responses at a systemic level. In this study, the Yale G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Some studies in children suggest possible relationships between TS and allergic diseases, such that more research is warranted to clarify the specific nature of these relationships (e.g., longitudinal relationship between variables, whether it is correlational, causal). Given that the neural basis of TDs are relatively understood, it will be important to understand whether and precisely how gut microbiota might impact relevant circuitry, as well as whether altered microbiota precede or are followed by the emergence of TD symptoms ( 22 24 ). The gut microbiota of allergic and non-allergic infants shows significant differences during the first year of life ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in children suggest possible relationships between TS and allergic diseases, such that more research is warranted to clarify the specific nature of these relationships (e.g., longitudinal relationship between variables, whether it is correlational, causal). Given that the neural basis of TDs are relatively understood, it will be important to understand whether and precisely how gut microbiota might impact relevant circuitry, as well as whether altered microbiota precede or are followed by the emergence of TD symptoms ( 22 24 ). The gut microbiota of allergic and non-allergic infants shows significant differences during the first year of life ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when children with allergic diseases are repeatedly exposed to allergens, the immune imbalance caused by them and the continuous attack of pro-inflammatory cytokines may be important mechanisms in inducing TD. children, mainly manifested by the decrease in the expression levels of CD3+ T cells, CD4+ T cells, and CD4+/CD8+ (48). Leckman found that the levels of pro-inflammatory cytokines such as TNF-α and IL-12 were increased in the peripheral blood of children with TD, and during the worsening of symptoms, the levels of these two cytokines further increased, suggesting that the occurrence of TD is related to innate immunity.…”
Section: Immunity and Tdmentioning
confidence: 99%
“…In 2021, Liu showed that allergic diseases increased the severity of TD childhood ( 48 ). In 2022, a meta-analysis provided strong evidence for a relationship between allergic diseases and TD: TD is positively associated with AA, AR, and AC ( 21 ).…”
Section: Correlation Between Allergic and Tdmentioning
confidence: 99%
“… 1 Allergic diseases, also called atopic diseases (“atopic” refers to the genetic susceptibility to developing allergy-related diseases), include allergic rhinitis, allergic conjunctivitis, allergic asthma, atopic dermatitis, food allergies, and urticaria. 2 Numerous studies have demonstrated that the high prevalence of allergic diseases is a significant risk factor for respiratory disorders, 3 tic disorders, 4 and autism spectrum disorders, 5 and they deserves widespread attention.…”
Section: Introductionmentioning
confidence: 99%